Effect of knee orthosis on walking performance in individuals with knee osteoarthritis - Jankaew, Amornthep; Sitilertpisan, Patraporn; Chamnongkich, Samatchai (Journal of Associated Medical Sciences, 2017)
Background: Knee orthosis has been recommended as part of conservative treatment for individuals with knee osteoarthritis (OA). However, the effects of common types of knee orthosis on function and pain during movement are still inconclusive. Objectives: To compare the effect of two types of knee orthosis (knee sleeve and OA knee brace) on walking variables and knee pain in individuals with mild to moderate severity of knee OA and to determine the association between knee pain and type of knee orthosis that the participants felt most satisfied with. Materials and methods: Twenty-four individuals (20 females and 4 males) diagnosed with knee OA participated in this study. Participants rated the overall knee pain they experienced in the past month, answered the Knee injury and Osteoarthritis Outcome Score (KOOS) and underwent a 40-meter fast paced walk test in three conditions: no-orthosis, knee sleeve, and OA knee brace. Walking time (second) and speed (meter/second) to complete the test were recorded. After each condition, the participants reported the level of pain during walking by a numerical rating scale (NRS). After completing all the tests, the participants indicated the type of knee orthosis that they felt most satisfied with. One-way repeated measure analysis of variance and Friedman test were used to compare the results from the three conditions. Spearman’s rho was used to examine the correlation between level of pain and the type of knee orthosis that participants chose. The level of significant was set at p<0.05. Results: Significant differences in walking time and speed were found between the three testing conditions (p<0.05). A reduction in walking time and an increased walking speed were revealed when either type of knee orthosis was worn with walking speed in decreasing order as followed: OA knee brace>knee sleeve>no-orthosis condition. Comparing with no-orthosis, OA knee brace and knee sleeve conditions significantly reduced pain (p<0.01). No significant difference in level of pain during walking between the two orthosis conditions was found (p=0.33). The correlation between the overall knee pain in the past month and the type of knee orthosis chosen was not significant (r=-0.354, p=0.09). Conclusion: Improvement in walking variables was found in knee OA patients with mild to moderate severity when either OA knee brace or knee sleeve was worn as compared to not wearing knee orthosis. In addition, both knee sleeve and OA knee brace aided in the reduction of knee pain during walking.